The Effect of Organizational Climate and Personality on Organizational Citizenship Behavior (OCB) With Work Motivation as a Mediating Variable: A Study of Teachers at Xin Zhong Elementary School in Surabaya - Wallesa, Hana; Pradiani, Theresia; Kibtiyah, Asriana (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: Quality education is a long-term investment that depends heavily on teachers’ professional commitment. At Xin Zhong Elementary School, a trilingual primary school in Surabaya with a multicultural teaching staff, variations in voluntary participation in extracurricular activities indicate differing levels of Organizational Citizenship Behavior (OCB). This study aims to analyze factors influencing OCB by examining organizational climate and personality (agreeableness), with work motivation as an intervening variable. Background Problems: The inconsistency of teachers’ voluntary involvement raises questions about how contextual and individual factors contribute to OCB and whether work motivation plays a mediating role in these relationships. Research Methods: This study employed a quantitative approach. The population consisted of all 60 primary school teachers at Xin Zhong Elementary School, using a census sampling technique. Data were collected through questionnaires distributed via Google Form and analyzed using SmartPLS 4.0. Findings/Results: The results show that organizational climate and personality have positive and significant effects on work motivation and OCB. Work motivation also has a positive and significant effect on OCB and mediates the influence of organizational climate and personality on OCB. Conclusion: The study concludes that organizational climate, personality, and work motivation are key determinants of teachers’ OCB, with motivation serving as an important mediating factor. Keywords: Organizational Citizenship Behavior (OCB); Organizational Climate; Agreeableness; Work Motivation.